Indo–US Security Cooperation: Implications for the Indian Ocean. (2nd January 2017) - Mishra, Vivek
ABSTRACT: There has been a clear growing maritime intent in India–US cooperation in the past few years and bilateral interests have come to converge, due to both the individual countries' interests and regional common goals. As an economically and militarily developing country, India seeks to expand its strategic influence the Indian Ocean Region (IOR). It also comes across as the most stable and powerful country in the region that could support the long-term interests of the US in the region. The US sees India as a significant balancer of China in the region, and the Indian Ocean as a maritime opponent to the South China Sea. As the US–China rivalry continues in the Asia-Pacific, the Indian Ocean remains the stable pivot from where the Asian power balance will be string-held. More importantly, going forward the Indian Ocean could be divided into maritime sub-regions of influence based on two emerging opposite power axes.